Smart grid load balancing methods to make an efficient heterogeneous network by using the communication cost function. Issue 3 (1st May 2018) - Kouhdaragh, Vahid; Amiri, Iraj Sadegh; Seyedi, Seyedalireza
Abstract : Different node types in smart grid (SG) system have different communication necessities. Different type of information such as power grid status and demand requests and responses are established between control station (CS) and different SG node types. Assigning the certain percentage of the nodes traffic to the radio access technologies (RATs) with respect to their cost functions (CFs) value can help to achieve this goal by defining the highest fitness degree between SG node type communication requirements and RATs communication characteristics to have an efficient load balance. In this study, the key performance indicators (KPIs) for CFs are the SG node communication requirements which are defined as data rate, delay, reliability, and security. The value of the work can be seen in node assigning method based on the CFs as a function of different RAT communication characteristics and node type communication requirements. The highest fitness degree between node communication needs and RAT characteristics are achieved in an efficient way which causes to make an efficient heterogeneous network. The work impact of using a certain RAT which has the best efficiency in sense of communication aspects by using a well‐defined CF is the innovation of this study as well.